Lung nodule volumetry: segmentation algorithms within the same software package cannot be used interchangeably. - Ashraf H; de Hoop B; Shaker SB; Dirksen A; Bach KS; Hansen H; Prokop M; Pedersen JH; Ashraf, H; de Hoop, B; Shaker, S B; Dirksen, A; et al. (European Radiology, 2010)
Objective: We examined the reproducibility of lung nodule volumetry software that offers three different volumetry algorithms.Methods: In a lung cancer screening trial, 188 baseline nodules >5 mm were identified. Including follow-ups, these nodules formed a study-set of 545 nodules. Nodules were independently double read by two readers using commercially available volumetry software. The software offers readers three different analysing algorithms. We compared the inter-observer variability of nodule volumetry when the readers used the same and different algorithms.Results: Both readers were able to correctly segment and measure 72% of nodules. In 80% of these cases, the readers chose the same algorithm. When readers used the same algorithm, exactly the same volume was measured in 50% of readings and a difference of >25% was observed in 4%. When the readers used different algorithms, 83% of measurements showed a difference of >25%.Conclusion: Modern volumetric software failed to correctly segment a high number of screen detected nodules. While choosing a different algorithm can yield better segmentation of a lung nodule, reproducibility of volumetric measurements deteriorates substantially when different algorithms were used. It is crucial even in the same software package to choose identical parameters for follow-up.